Coxsackievirus A24 causing acute conjunctivitis in a 2023 outbreak in Vietnam - Tran, Huy; Ha, Thao; Hoang, Linh; Tran, Yen; Ruder, Kevin; Liu, YuHeng; Yu, Danny; Abraham, Thomas; Hinterwirth, Armin; Deiner, Michael; Porco, Travis C.; Lietman, Thomas M.; et al. (International journal of infectious diseases, 2024)
•RNA-sequence analysis can identify causes of conjunctivitis outbreaks.•Coxsackievirus A24 was likely responsible for a conjunctivitis epidemic in Asia in 2023.•Purulence and itching can be seen commonly with viral eye infections.•Phylogenic analysis links this coxsackie virus to similar outbreaks worldwide. To determine the associated pathogen during the 2023 conjunctivitis outbreak in Vietnam RNA-sequencing was used to identify pathogens before and during the outbreak. 24 patients with infectious conjunctivitis between March and October 2023 from Hai Yen Vision Institute in Vietnam were swabbed. Coxsackievirus A24v was the most common pathogen identified. Phylogenetic analysis of these strains demonstrates similarities to the Coxsackievirus identified in the 2022 India outbreak. Human adenovirus D was also circulating. Ocular findings of tearing, purulence, and itching were common in this outbreak. Multiple viruses can co-circulate during conjunctivitis outbreaks. Hemorrhagic conjunctivitis, commonly associated with coxsackievirus conjunctivitis, was not a common clinical sign in this outbreak. Repeat genetic surveillance, with the notable inclusion of RNA virus detection strategies, is important for outbreak detection.